1992
DOI: 10.1056/nejm199206253262605
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Leukemia after Chemotherapy and Radiation Treatment for Breast Cancer

Abstract: Although leukemia occurs in few patients with breast cancer, significantly elevated risks were linked to treatments with regional radiation and alkylating agents. Melphalan is a more potent leukemogen than cyclophosphamide or radiotherapy. Low risks were associated with the levels of cyclophosphamide in common use today. Systemic drug therapy combined with radiotherapy that delivers high doses to the marrow appears to enhance the risk of leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
209
0
10

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(232 citation statements)
references
References 18 publications
10
209
0
10
Order By: Relevance
“…24 In other studies, relative risks in the order of 2.0-2.4 have been observed following radiotherapy. 32,33 This indicates that approximately 50% of such AMLs are directly radiation induced, whereas another 50% are cases of de novo AML. Hence, cases 29, 52 and 148, as well as case R treated with methotrexate þ prednisone without a confirmed leukemogenic potential, could all be suspected to represent de novo leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…24 In other studies, relative risks in the order of 2.0-2.4 have been observed following radiotherapy. 32,33 This indicates that approximately 50% of such AMLs are directly radiation induced, whereas another 50% are cases of de novo AML. Hence, cases 29, 52 and 148, as well as case R treated with methotrexate þ prednisone without a confirmed leukemogenic potential, could all be suspected to represent de novo leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…Bone Marrow Transplantation (2003) 32, 1153-1157. doi:10.1038/sj.bmt.1704291 Keywords: high-dose chemotherapy; adjuvant therapy; breast cancer; mitoxantrone; secondary AML Secondary myelodysplasia (MDS) or acute myeloid leukemia (AML) in breast cancer patients is a rare but wellknown long-term complication of prior chemotherapy or radiation therapy as adjuvant therapy. [1][2][3] Specific risk factors are the combinations of chemotherapy and radiation therapy, the cumulative dose of alkylating agents and the duration of therapy. 2 Two different types of treatmentrelated leukemia can be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Specific risk factors are the combinations of chemotherapy and radiation therapy, the cumulative dose of alkylating agents and the duration of therapy. 2 Two different types of treatmentrelated leukemia can be distinguished. The first type results from prior therapy with alkylating agents or radiation therapy, and occurs after a latency period of 5-7 years.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our results suggest that almost all of the excess leukaemia cases occurring in cancer patients who had received radiotherapy are in breast cancer survivors. The elevated risks of acute nonlymphocytic leukaemia following breast cancer has been ascribed primarily to alkylating agent chemotherapy, with radiotherapy possibly adding to this risk, [12][13][14] and some studies have suggested that adjuvant radiotherapy without chemotherapy may also confer a small increased risk of leukaemia, with risks rising in relation to increasing bone marrow dose. 12,15 We have no information on the joint distribution of chemotherapy and radiotherapy from the SEER study, so the possibility of confounding by chemotherapy must be considered.…”
Section: Risk Due To Radiotherapymentioning
confidence: 99%